Students' Valence Perceptions of Final Results - Arwani, Ahmad Muhbib; Khambali, Imam; fitriana, Aprilia indah (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2025)
This article examines the dynamics of motivation in higher education, particularly in relation to Expectancy Theory, which highlights the aspect of valence. The main focus of this research is on students' perceptions of valence, namely the extent to which students attach value or attractiveness to achieving final outcomes (academic grades) as a reward for their efforts. Through a literature review of various academic journals and educational psychology theories, this article aims to identify and analyze factors that influence students' valence and its relevance to academic performance. Using a library research and content analysis approach, this study concludes that the perception of valence toward final outcomes is influenced not only by value orientations but also by students' interpretations of the quality of learning, providing educators with deeper insights into designing evaluation systems that motivate both intrinsically and extrinsically